2001
DOI: 10.1109/32.922713
|View full text |Cite
|
Sign up to set email alerts
|

An internally replicated quasi-experimental comparison of checklist and perspective based reading of code documents

Abstract: ÐThe basic premise of software inspections is that they detect and remove defects before they propagate to subsequent development phases where their detection and correction cost escalates. To exploit their full potential, software inspections must call for a close and strict examination of the inspected artifact. For this, reading techniques for defect detection may be helpful since these techniques tell inspection participants what to look for and, more importantly, how to scrutinize a software artifact in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 61 publications
(109 reference statements)
1
63
0
2
Order By: Relevance
“…Thus, such common defect types existing in the literature occurs in the studies of Brykczynski (1999;Biffl and Halling, 2000;Laitenberger et al, 2001;Sabaliauskaite et al, 2002a;2004;Thelin et al, 2003;Denger and Paech, 2004;Cox et al, 2004a;Staron et al, 2005;Mohammed et al, 2015). A brief discussion of each study of such techniques/approaches is presented as follows:…”
Section: Research Question 2 (Rq2a and Rq2b)mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, such common defect types existing in the literature occurs in the studies of Brykczynski (1999;Biffl and Halling, 2000;Laitenberger et al, 2001;Sabaliauskaite et al, 2002a;2004;Thelin et al, 2003;Denger and Paech, 2004;Cox et al, 2004a;Staron et al, 2005;Mohammed et al, 2015). A brief discussion of each study of such techniques/approaches is presented as follows:…”
Section: Research Question 2 (Rq2a and Rq2b)mentioning
confidence: 99%
“…In summary, the studies presented in this section answered RQ2 and provide evidence of the existing inspection techniques or approaches associated with defect types, encompassing studies, such as: (i) several academic validation studies that compare and evaluate the effectiveness of the main inspection techniques (e.g., CBR, PBR, SBR, Ad hoc, among others) in distinct contexts (Biffl and Halling, 2000;Cox et al 2004a;Denger and Paech, 2004;Laitenberger et al, 2001;Mohammed et al, 2015;Sabaliauskaite et al, 2002a;2003;Staron et al, 2005;Thelin et al, 2003); (ii) case studies in industry (Felderer et al, 2014;Ma et al, 2014; and (iii) application and adaptation of systematic classifications such as ODC (Gopinath et al, 2014;Ma et al 2014;.…”
Section: Research Question 2 (Rq2a and Rq2b)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of these experiments do not give a conclusive answer to the research question. Some experiments showed that SBR techniques are more effective and efficient than CBR [3,15,18,22,23,26], while other experiments failed to show any significant difference between the techniques [9,11,20,24].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of studies has demonstrated that reading techniques are effective for improving individual review practices in different domains and types of inspection, e.g. natural language requirements [3], requirements in formal notation [20], high-level designs [14], code [13,15], and user interfaces [32].…”
Section: Introductionmentioning
confidence: 99%